Assessment of vegetable farmers’ attitude towards certification scheme for Malaysian good agricultural practices - Gom, Elina W. (2016)
Farmers are the main focus in ensuring the vegetables in our country are at its best quality and is safe to be consumed. The nutritional facts of vegetables which entail health benefits to consumers have led to an increase in the demand for fresh quality vegetables. However, foodborne illness outbreaks and environmental abuse due to the use of excessive pesticides have caused not just consumers but also the government to become increasingly concerned about vegetable safety and quality. Good Agricultural Practices (GAP) is the answer to this crisis. GAP emphasizes on environment, economy and social aspects of farming to ensure that the products are safe to consume and the farming operations are sustainable, worker friendly and environmentally safe. In Malaysia, the government introduced GAP standards namely Certification Scheme for Good Agricultural Practices (MyGAP) in order to recognize fruits and vegetable farms that adopt GAP. Along with this, the government has also been providing non-mandatory training and courses, having extensions, giving promotions and exhibitions to attract farmers to the MyGAP certification scheme. However, despite all efforts to encourage the farmers to get the certification, the uptake among Malaysian farmers is still low and slow. Thus this study intends to uncover the underlying factors that could influence vegetable farmers’ assigned values and consequently their attitudes towards good agricultural practices under the MyGAP certification scheme. A survey was conducted in Peninsular Malaysia where 263 respondents were interviewed through a structured questionnaire. The study is made up of two groups of respondents: (1) Vegetable farmers with MyGAP; and (2) vegetable farmers without MyGAP. An Assigned Value Model was employed in the study and descriptive analysis; chi-square analysis; independent samples t-test; as well as multiple regression were used to analyze the collected data. The results suggested that vegetable farmers with MyGAP and without MyGAP are significantly different in terms of their attitude, underlying values, assigned values, knowledge and personal norms. In addition, it was also found that there is a significant association between the farmers’ demographic profiles and MyGAP endorsement. Underlying values, knowledge and personal norms were found to have a significant relationship with the assigned values of vegetable farmers with MyGAP; which then leads to a significant relationship of assigned values and knowledge in shaping their attitudes. While for the farmers without MyGAP, underlying values, knowledge, personal norms and perceived barriers were found to have a significant relationship with the assigned values of farmers; which then leads to a significant relationship of assigned values and perceived barriers in shaping the attitude, whereas knowledge did not show any significant relationship with the attitude of vegetable farmers without MyGAP. To move forward, policy makers should consider a number of principles to make this scheme worthwhile. Focusing profoundly on the values, self-standards, level of knowledge, and the barriers that prevent the farmers in participating in this scheme in order expand the attitude of the farmers in building a strong and convincing foundation for Malaysia to increase vegetable safety and quality in the future.